2022
DOI: 10.3390/ijerph191710548
|View full text |Cite
|
Sign up to set email alerts
|

Local Hyperbaric Oxygen Therapy in the Treatment of Diabetic Foot Ulcers

Abstract: Background: Diabetes mellitus is one of the most common metabolic diseases. The most serious complication of diabetes is diabetic foot ulcer, which affects several million people around the world each year. In recent years, increasingly modern methods of physical medicine including hyperbaric oxygen therapy have been used often in the complex therapy of this complication. Methods: This study included 45 patients, 24 male (53.3%) and 21 female (46.6%), whose age was between 49 and 83 years (mean age: 66.7 ± 8.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(21 reference statements)
0
8
0
1
Order By: Relevance
“…17 tests that were published between 1992 and 2022 were included in the meta‐analysis after an evaluation of 957 applicable exams since they fit the inclusion criteria 16,22–37 . Table 2 summarises the findings of these investigations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 tests that were published between 1992 and 2022 were included in the meta‐analysis after an evaluation of 957 applicable exams since they fit the inclusion criteria 16,22–37 . Table 2 summarises the findings of these investigations.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 18 to 5466 people. 16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The examined data revealed that hyperbaric oxygen treatment had significantly higher healed ulcers, higher adverse events, lower mortality and higher ulcer area reduction compared to standard treatment in patients with diabetic foot ulcers. However, hyperbaric oxygen treatment and standard treatment had no significant difference in amputation, major amputation, minor amputation and healing time in patients with diabetic foot ulcers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It exerts a beneficial impact on the entire process of open wound repair. Frykberg 17 found that local oxygen therapy effectively treats chronic wounds, while Pasek and Szajkowski 18 noted that local hyperbaric oxygen therapy accelerates the healing process of diabetic foot ulcers, as evidenced by objective evaluation, and reduces pain perception. The results of this study demonstrated that the study group exhibited shorter wound healing time and hospital stay compared to the control group ( p < 0.05), consistent with the findings of previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Local HBOT treatment is the new treatment for diabetic foot ulcer (DFU) and venous leg ulcers first published by Pasek J. et al in 2022 and 2023. 52,53 It reported promising results in wound area and pain reduction. However, the data on this new treatment in postrevascularization ulcers is unavailable.…”
Section: Options For Oxygen Therapymentioning
confidence: 99%